Metal ceramic with strong grain growth orientation on the surface and preparation method thereof

By introducing an oxygen atmosphere into the sintering process of metal cermets to form a lean bond phase, a Ti(O,C,N) surface layer with strong grain growth orientation was prepared, which solved the collapse of uncoated metal cermet tools at high linear speeds. The problem of loss improves wear resistance and chemical stability, extends tool life and improves processing performance.

CN118932234BActive Publication Date: 2025-01-03GANZHOU ACHTECK TOOL TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411382973.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing uncoated cermet tools are prone to sudden collapse at high linear speeds, reducing tool life and affecting the surface finish of the processed parts, making it difficult to meet the needs of high-speed and high-precision cutting.

Method used

A metal cermet with a strong grain growth orientation on the surface layer, and its surface layer is a face-centered cubic crystal structure with a uniform orientation of more than 80% and a large aspect ratio of uniform diameter. By introducing an oxygen atmosphere in the sintering process, it forms a lean bond phase, combined with high pressure Conditional sintering was performed to prepare a Ti(O,C,N) surface layer with extremely high hardness and wear resistance.

Benefits of technology

It significantly improves the material's resistance to bond wear, chemical stability, heat resistance and oxidation resistance, extends the tool life, and improves the processing performance, and the performance is close to the effect of coating treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118932234B_ABST
    Figure CN118932234B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of metal ceramics, and specifically relates to a metal ceramic with a strong grain growth orientation on the surface and a preparation method thereof, wherein an oxygen atmosphere is introduced into the sintering process to form a Ti(O,C,N) surface region with a face-centered cubic crystal structure that is poor in bonding phase, dense, and has more than 80% uniform orientation and large aspect ratio grains on the surface of the material. Titanium carbides and nitrides have extremely high hardness and wear resistance, and the compactness and self-lubricating property of titanium oxides make the organizational structure have good resistance to bonding and wear, relatively stable chemical properties, heat resistance, corrosion resistance, and oxidation resistance, thereby improving the processing performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal ceramics, and in particular relates to a metal ceramic with a surface layer having a strong grain growth orientation and a preparation method thereof. Background Art

[0002] Ti(C,N)-based cermets are upgraded alternative materials for cemented carbide materials. With their higher wear resistance, lower friction coefficient between metals, better high temperature performance and oxidation resistance, cermet tools can adapt well to high-speed, high-precision and continuous, dry cutting with larger feed volume, greatly improving cutting efficiency and service life. Ti(C,N)-based cermets are made by powder metallurgy using soft transition metals (Ni, Co) bonded with ceramic matrix phases such as TiC, TiN, Ti(C,N) and secondary carbides (such as Mo2C, WC, TaC, etc.). Compared with cemented carbide tools, Ti(C,N)-based cermets have better affinity for iron and high temperature strength. They are a composite material with high hardness and high wear resistance. They are widely used in the field of high-speed precision cutting to obtain good surface finish. With the current demand for increasing processing efficiency, the processing speed of cermet processing is required to be further improved. The general solution is to coat ordinary cermets. Uncoated cermets are prone to sudden breakage when facing high line speeds, which reduces tool life and affects the surface finish of the workpiece. There is still room for improvement in order to obtain uncoated cermet tools and preparation methods that are more suitable for high line speed and high wear resistance machining of steel materials. Summary of the invention

[0003] In order to solve the problems existing in the prior art, the main purpose of the present invention is to provide a metal ceramic with a strong grain growth orientation on the surface and a preparation method thereof.

[0004] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:

[0005] A metal ceramic with a surface layer having a strong grain growth orientation, which has a Ti (O, C, N) surface layer with a face-centered cubic crystal structure and more than 80% uniformly oriented grains with a large aspect ratio.

[0006] As a preferred solution of the metal ceramic with a surface layer having a strong grain growth orientation described in the present invention, the thickness of the surface layer is 1-10 μm.

[0007] As a preferred embodiment of the metal ceramic with a surface layer having a strong grain growth orientation described in the present invention, the large aspect ratio is greater than 3.

[0008] As a preferred embodiment of the metal ceramic with a surface layer having a strong grain growth orientation described in the present invention, the surface layer is a poor binder phase.

[0009] As a preferred embodiment of the metal ceramic with a surface layer having a strong grain growth orientation described in the present invention, the grain growth orientation of the metal ceramic with a surface layer having a strong grain growth orientation is [1,1,1].

[0010] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:

[0011] A method for preparing a metal ceramic having a surface layer with a strong grain growth orientation comprises the following steps:

[0012] S1, mixing the raw materials, solvent and forming agent, ball milling and spray granulation to obtain a mixed material;

[0013] S2, pressing the mixed material into a compact to obtain a green compact;

[0014] S3, placing the compact in a vacuum atmosphere, raising the temperature to the forming agent removal temperature, removing the forming agent, then sintering the compact from which the forming agent has been removed in a nitrogen and oxygen mixed gas micro-pressure atmosphere, and finally sintering under high pressure conditions and then cooling to room temperature to obtain a metal ceramic with a strong grain growth orientation on the surface.

[0015] As a preferred embodiment of the method for preparing a metal ceramic with a surface layer having a strong grain growth orientation described in the present invention, in which: in the step S1, the raw material includes hard phase powder and binding phase powder, the mass of the hard phase powder accounts for 80~90wt% of the total mass of the raw material, and the mass of the binding phase powder accounts for 10~20wt% of the total mass of the raw material.

[0016] As a preferred embodiment of the method for preparing a metal ceramic with a strong grain growth orientation on the surface described in the present invention, wherein: in the step S1, the hard phase powder is at least one of carbide powder, nitride powder or carbonitride powder of Ti and at least one of carbide powder, nitride powder or carbonitride powder containing more than one of W, Mo, Ta, Nb, V, Cr, Zr and their solid solution powders; the binding phase powder is selected from at least one of cobalt, nickel and iron; the molding agent is selected from at least one of 48#-56# paraffin and PEG1000-PEG20000; and the solvent is anhydrous ethanol.

[0017] As a preferred embodiment of the method for preparing a metal ceramic with a surface layer having a strong grain growth orientation described in the present invention, wherein: in the step S1, the particle size of the hard phase powder and the bonding phase powder is less than 1.5 μm.

[0018] As a preferred embodiment of the method for preparing a metal ceramic having a surface layer with a strong grain growth orientation described in the present invention, in said step S3, the forming agent removal temperature is 1200°C.

[0019] As a preferred embodiment of the method for preparing a metal ceramic with a strong grain growth orientation on the surface described in the present invention, wherein: in the step S3, the sintering process in a micro-pressure atmosphere of a nitrogen and oxygen mixed gas is: the atmosphere has a nitrogen partial pressure of 30~50mbar and an oxygen partial pressure of 50~70mbar, and the temperature is increased and sintered to 1440~1460℃ in a micro-pressure atmosphere of a nitrogen and oxygen mixed gas at a heating rate of 5~7℃ / min.

[0020] As a preferred embodiment of the method for preparing a metal ceramic with a surface layer having a strong grain growth orientation described in the present invention, in the step S3, sintering under high pressure conditions is: keeping the temperature at 1440-1460°C for 1-2 hours in a 90 bar high pressure argon atmosphere.

[0021] The beneficial effects of the present invention are as follows:

[0022] The present invention proposes a metal ceramic with a strong grain growth orientation on the surface and a preparation method thereof. By introducing an oxygen atmosphere in the sintering process, a Ti(O,C,N) surface region with a face-centered cubic crystal structure that is poor in bonding phase, dense, and has more than 80% uniform orientation and large aspect ratio grains is formed on the surface of the material. Titanium carbides and nitrides have extremely high hardness and wear resistance, and the compactness and self-lubricating properties of titanium oxides make the organizational structure have good resistance to bonding and wear, relatively stable chemical properties, heat resistance, corrosion resistance, and oxidation resistance, and improve the processing performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0024] Figure 1 This is a cross-sectional view of the metal ceramic prepared in Example 1 of the present invention.

[0025] Figure 2 for Figure 1 A partial enlarged view of the cross-sectional view.

[0026] Figure 3 for Figure 2 A partial enlarged view of .

[0027] Figure 4 This is a cross-sectional view of the metal ceramic prepared in Comparative Example 1.

[0028] Figure 5 This is a cross-sectional view of the metal ceramic prepared in Comparative Example 2.

[0029] Figure 6 This is a cross-sectional view of the metal ceramic prepared in Comparative Example 3.

[0030] In the figure, 1-strong grain growth orientation layer, 2-internal core structure area.

[0031] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0032] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] According to one aspect of the present invention, the present invention provides the following technical solution:

[0034] A metal ceramic with a surface layer having a strong grain growth orientation, which has a Ti (O, C, N) surface layer with a face-centered cubic crystal structure and more than 80% uniformly oriented grains with a large aspect ratio.

[0035] Preferably, the surface layer has a thickness of 1 to 10 μm, the large aspect ratio is greater than 3, and the surface layer is a binder-poor layer.

[0036] Preferably, the grain growth orientation of the metal ceramic with a strong grain growth orientation on the surface layer is [1,1,1].

[0037] According to another aspect of the present invention, the present invention provides the following technical solution:

[0038] A method for preparing a metal ceramic having a surface layer with a strong grain growth orientation comprises the following steps:

[0039] S1, mixing the raw materials, solvent and forming agent, ball milling and spray granulation to obtain a mixed material;

[0040] S2, pressing the mixed material into a compact to obtain a green compact;

[0041] S3, placing the compact in a vacuum atmosphere, raising the temperature to the forming agent removal temperature, removing the forming agent, then sintering the compact from which the forming agent has been removed in a nitrogen and oxygen mixed gas micro-pressure atmosphere, and finally sintering under high pressure conditions and then cooling to room temperature to obtain a metal ceramic with a strong grain growth orientation on the surface.

[0042] Preferably, in step S1, the raw material includes hard phase powder and binder phase powder, the mass of the hard phase powder accounts for 80-90wt% of the total mass of the raw material, and the mass of the binder phase powder accounts for 10-20wt% of the total mass of the raw material. Specifically, the mass of the hard phase powder can be, for example, any one of 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt%, 90wt% of the total mass of the raw material, or a range between any two thereof, and the mass of the binder phase powder can be, for example, any one of 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt% of the total mass of the raw material, or a range between any two thereof.

[0043] Preferably, in step S1, the hard phase powder is at least one of carbide powder, nitride powder or carbonitride powder of Ti and at least one of carbide powder, nitride powder or carbonitride powder containing more than one of W, Mo, Ta, Nb, V, Cr, Zr and their solid solution powders; the binding phase powder is selected from at least one of cobalt, nickel and iron; the molding agent is selected from at least one of 48#-56# paraffin wax and PEG1000-PEG20000, and the amount of the molding agent added is 2wt% of the total mass of the raw material; and the solvent is anhydrous ethanol.

[0044] Preferably, in step S1, the particle size of the hard phase powder and the binder phase powder is less than 1.5 μm.

[0045] Preferably, in step S3, the forming agent removal temperature is 1200°C. The sintering process in a nitrogen and oxygen mixed gas micro-pressure atmosphere is: the atmosphere is a nitrogen partial pressure of 30-50 mbar and an oxygen partial pressure of 50-70 mbar, and the temperature is raised to 1440-1460°C at a heating rate of 5-7°C / min in a nitrogen and oxygen mixed gas micro-pressure atmosphere. Sintering under high pressure conditions is: in a 90 bar high-pressure argon atmosphere, keep warm at 1440-1460°C for 1-2 hours. Specifically, in a nitrogen and oxygen mixed gas micro-pressure atmosphere, the nitrogen partial pressure can be, for example, any one of 30 mbar, 35 mbar, 40 mbar, 45 mbar, 50 mbar or a range between any two, and the oxygen partial pressure can be, for example, any one of 50 mbar, 55 mbar, 60 mbar, 65 mbar, 70 mbar or a range between any two.

[0046] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0047] Example 1

[0048] A method for preparing a metal ceramic having a surface layer with a strong grain growth orientation comprises the following steps:

[0049] S1. The raw materials are cobalt powder and nickel powder as binder phase powder, titanium-containing cubic carbonitride powder and tungsten, tantalum, niobium and molybdenum carbide powder as hard phase powder. The mass percentage of each raw material is as follows: binder phase powder (the mass ratio of cobalt powder and nickel powder is 1:1) 15wt%, tantalum and niobium carbide powder (the mass ratio of tantalum carbide and niobium carbide is 4:1) 10wt%, molybdenum carbide powder 5wt%, titanium-containing cubic carbonitride 55wt%, and the rest is tungsten carbide powder. The particle size of each powder is <1.5 μm. The above raw materials, solvent (using anhydrous ethanol as solvent) and molding agent (using paraffin as molding agent, the addition amount is 2wt% of the total mass of the raw materials) are mixed and ball-milled, and spray granulated to obtain a mixture;

[0050] S2, pressing the mixed material into a compact to obtain a green compact;

[0051] S3. Place the pressed green sheet in a vacuum atmosphere, heat it to 1200°C, introduce a mixed gas to form a mixed atmosphere of 50 mbar nitrogen partial pressure and 50 mbar oxygen partial pressure, then heat and sinter it to 1450°C at a heating rate of 6°C / min in the mixed atmosphere, then switch to a 90 bar high-pressure argon atmosphere, keep warm at 1450°C for 1.5 hours, and then cool it to room temperature to obtain a metal ceramic with a strong grain growth orientation on the surface.

[0052] The metal ceramic with a strong grain growth orientation on the surface obtained in this embodiment (its cross section is as follows Figure 1-3 As shown, Figure 1 1 in the figure is a strong grain growth orientation layer. Figure 1 The tool A1 is obtained by cutting and forming the tool blank (2 in the figure is the internal core structure area) and rounding the cutting edge of the tool with a nylon brush containing SiC.

[0053] Example 2

[0054] A method for preparing a metal ceramic having a surface layer with a strong grain growth orientation comprises the following steps:

[0055] S1. The raw materials are cobalt powder and nickel powder as binder phase powder, titanium-containing cubic carbonitride powder and tungsten, tantalum, niobium and molybdenum carbide powders as hard phase powders. The mass percentage of each raw material is as follows: binder phase powder (the mass ratio of cobalt powder and nickel powder is 1:1) 20wt%, tantalum and niobium carbide powders (the mass ratio of tantalum carbide and niobium carbide is 4:1) 10wt%, molybdenum carbide powder 5wt%, titanium-containing cubic carbonitride 55wt%, and the remainder is tungsten carbide powder. The particle size of each powder is <1.5 μm. The above raw materials, solvent (using anhydrous ethanol as solvent) and molding agent (using paraffin as molding agent, the addition amount is 2wt% of the total mass of the raw materials) are mixed and ball-milled, and spray granulated to obtain a mixture;

[0056] S2, pressing the mixed material into a compact to obtain a green compact;

[0057] S3. Place the pressed green sheet in a vacuum atmosphere, heat it to 1200°C, introduce a mixed gas to form a mixed atmosphere of 30 mbar nitrogen partial pressure and 70 mbar oxygen partial pressure, then heat and sinter it to 1450°C at a heating rate of 6°C / min in the mixed atmosphere, then switch to a 90 bar high-pressure argon atmosphere, keep warm at 1450°C for 1.5 hours, and then cool it to room temperature to obtain a metal ceramic with a strong grain growth orientation on the surface.

[0058] The metal ceramic with a strong grain growth orientation on the surface obtained in this embodiment was cut and formed to form a rough cutter blank, and the cutting edge of the cutter was rounded using a nylon brush containing SiC to obtain a cutter A2.

[0059] Comparative Example 1

[0060] The difference from Example 1 is that in step S3, the temperature is raised to 1450° C. under vacuum atmosphere, then switched to 90 bar high-pressure argon atmosphere, kept at 1450° C. for 0.5 h, and then cooled to room temperature.

[0061] The metal ceramic (whose cross section is as shown in FIG. Figure 4 (as shown) the insert was wet-sandblasted at an angle of 45° to the front cutting edge of the insert to round the cutting edge to obtain tool B1.

[0062] Comparative Example 2

[0063] The difference from Example 1 is that in step S3, the temperature is raised to 1450° C. under vacuum atmosphere, then switched to 90 bar high-pressure argon atmosphere, kept at 1450° C. for 0.5 h, and then cooled to room temperature.

[0064] The metal ceramic (whose cross section is as shown in FIG. Figure 5(As shown in the figure), the insert was wet-sandblasted at an angle of 45° to the front cutting edge of the insert to round the cutting edge, and then an AlTiN coating was deposited on the surface with a coating thickness of 3 μm to obtain tool B2.

[0065] Comparative Example 3

[0066] The difference from Example 1 is that in step S3, the temperature is raised to 1450°C under the conditions of nitrogen partial pressure of 200 mbar and oxygen partial pressure of 100 mbar, and then switched to 90 bar high-pressure argon atmosphere, and kept at 1450°C for 0.5 h, and then cooled to room temperature.

[0067] The metal ceramic (whose cross section is as shown in FIG. Figure 6 (As shown in the figure), the insert was wet-sandblasted at an angle of 45° to the front cutting edge of the insert to round the cutting edge to obtain tool B3.

[0068] The wear resistance of the blades prepared in the above-mentioned Examples 1-2 and Comparative Examples 1-3 was compared and tested by longitudinal turning of 40CrNi2Mo steel bars. The tool life standard is the processing time when the back tool wear is 0.3 mm. The cutting conditions are shown in Table 1:

[0069] Table 1

[0070]

[0071] The test results are detailed in Table 2:

[0072] Table 2

[0073]

[0074] The anti-oxidation performance of the knives prepared in the above Examples 1-2 and Comparative Examples 1-3 was compared and tested. The knife samples were placed in a tube furnace and kept warm for 3 hours at an air flow rate of 1 L / min and a temperature of 900°C. The weight gain of the knives was measured. The weight gain results are shown in Table 3:

[0075] Table 3

[0076]

[0077] The test results show that when the cutting tool of the embodiment of the present invention is kept warm for 3 hours at an air flow rate of 1 L / min and a temperature of 900° C., the weight gain of the cutting tool is ≤0.030 g, which is much lower than the weight gain of the cutting tool of the comparative example.

[0078] In the high-speed turning of steel, the embodiments of the present invention, without preparing a coating, introduce an oxygen atmosphere in the sintering process to form a Ti(O,C,N) surface layer region on the material surface that is poor in bonding phase, dense, has a uniform orientation of more than 80%, and a face-centered cubic crystal structure with a large aspect ratio of grains. The performance of the surface layer is significantly better than that of the comparative example 1, and is close to that of the comparative example 2 in which a coating is prepared on the surface. The surface layer has good resistance to bonding and wear, relatively stable chemical properties, heat resistance, corrosion resistance, and oxidation resistance, and improves the processing performance of the material. Under high nitriding pressure and oxygen pressure, the comparative example 3 has a second hard phase segregation and η phase inside the alloy structure, and the brittleness increases.

[0079] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A metal ceramic having a surface layer with a strong grain growth orientation, characterized in that: It has a Ti(O,C,N) surface layer with a face-centered cubic crystal structure and more than 80% uniformly oriented, large aspect ratio grains, an aspect ratio greater than 3, and a grain growth orientation of [1,1,1].

2. The metal ceramic having a surface layer with a strong grain growth orientation according to claim 1, characterized in that: The surface layer thickness is 1-10 μm.

3. The metal ceramic having a surface layer with a strong grain growth orientation according to claim 1, characterized in that: The surface layer is a poor binder phase.

4. A method for preparing a metal ceramic having a surface layer with strong grain growth orientation as claimed in any one of claims 1 to 3, characterized in that: The steps include: S1, mixing the raw materials, solvent and forming agent, ball milling and spray granulation to obtain a mixed material; S2, pressing the mixed material into a compact to obtain a green compact; S3, placing the compact under a vacuum atmosphere, heating it to the forming agent removal temperature, removing the forming agent, and then sintering the compact from which the forming agent has been removed in a nitrogen and oxygen mixed gas micro-pressure atmosphere, and finally cooling it to room temperature after sintering under high pressure conditions to obtain a metal ceramic with a strong grain growth orientation on the surface; the sintering process in a nitrogen and oxygen mixed gas micro-pressure atmosphere is as follows: the atmosphere has a nitrogen partial pressure of 30-50 mbar and an oxygen partial pressure of 50-70 mbar, and the temperature is increased and sintered to 1440-1460°C in a nitrogen and oxygen mixed gas micro-pressure atmosphere at a heating rate of 5-7°C / min; sintering under high pressure conditions is as follows: in a 90 bar high-pressure argon atmosphere, keeping warm at 1440-1460°C for 1-2 hours.

5. The method for preparing a metal ceramic having a surface layer with a strong grain growth orientation according to claim 4, characterized in that: In step S1, the raw material includes hard phase powder and binder phase powder, the mass of the hard phase powder accounts for 80-90wt% of the total mass of the raw material, and the mass of the binder phase powder accounts for 10-20wt% of the total mass of the raw material.

6. The method for preparing a metal ceramic having a surface layer with a strong grain growth orientation according to claim 4, characterized in that: In the step S1, the hard phase powder is at least one of carbide powder, nitride powder or carbonitride powder of Ti and at least one of carbide powder, nitride powder or carbonitride powder containing more than one of W, Mo, Ta, Nb, V, Cr and Zr, and the hard phase powder is not all nitride powder; the binding phase powder is selected from at least one of cobalt, nickel and iron; the molding agent is selected from at least one of 48#-56# paraffin and PEG1000-PEG20000; and the solvent is anhydrous ethanol.